THE IMPACT OF GOOD CORPORATE GOVERNANCE, DIVIDEND POLICY, FIRM SIZE, PROFITABILITY, AND LEVERAGE TOWARDS EARNINGS MANAGEMENT IN STATE-OWNED ENTERPRISES LISTED AT INDONESIA STOCK EXCHANGE - Arifin Arifin; Ivany Wardhana (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
Earning profits is one of the objectives for company to look good in the eyes of public and potential investors which become an opportunity for the management to intervene in the preparation of financial statement through earnings management due to the different interests between the principals and the agents. The objective of this research is to analyze the impact of good corporate governance, dividend policy, firm size, profitability, and leverage toward earnings management in state-owned enterprises listed at Indonesia Stock Exchange (IDX) during the period 2016-2020. The population of this research is the state-owned enterprises listed in Indonesia Stock Exchange during 2016-2020. Further, with the employed purposive sampling and determined criteria, 11 companies are chosen as the samples. The data analysis method applied is multiple linear regression which processed through SPSS 25. The result of this research shows that good corporate governance and firm size have an insignificant positive impact toward earnings management partially, dividend policy and profitability have a significant negative impact toward earnings management partially, and leverage has an insignificant negative impact toward earnings management partially. On the other hand, good corporate governance, dividend policy, firm size, profitability, and leverage have significant simultaneous impact toward earnings management.